2020
DOI: 10.3390/cancers12113404
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Cell Therapy and Cancer Vaccine in Biliary Tract Cancers (BTCs)

Abstract: Biliary tract cancer (BTC) is a rare, but aggressive, disease that comprises of gallbladder carcinoma, intrahepatic cholangiocarcinoma and extrahepatic cholangiocarcinoma, with heterogeneous molecular profiles. Advanced disease has limited therapeutic options beyond first-line platinum-based chemotherapy. Immunotherapy has emerged as a viable option for many cancers with a similar unmet need. Therefore, we reviewed current understanding of the tumor immune microenvironment and recent advances in cellular immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The hot tumor (IS2) corresponded to a more complex TME. Inflammatory cytokines, such as, interleukin, tumor necrosis factor and TGF-β, play key roles in tumor progression and promotion of early metastasis (Han et al, 2020). Although IS2 exhibited increased immune cell infiltration, the survival of IS2 patients was worse than that of IS1.…”
Section: Discussionmentioning
confidence: 99%
“…The hot tumor (IS2) corresponded to a more complex TME. Inflammatory cytokines, such as, interleukin, tumor necrosis factor and TGF-β, play key roles in tumor progression and promotion of early metastasis (Han et al, 2020). Although IS2 exhibited increased immune cell infiltration, the survival of IS2 patients was worse than that of IS1.…”
Section: Discussionmentioning
confidence: 99%
“…As in HCC cases, also in CCA vaccines development are also reported, such as the DC and peptide vaccines, however without presenting adequately favorable anti-neoplastic results [ 74 ], mainly attributed to T cell exclusion mechanism and TME-associated immunosuppression, by which TME prevent the aggregation of T cells that can induce harmful effects to tumors. T cell exclusion constitutes a difficult task to be faced for the achievement of the optimal response to immunotherapy [ 75 ].…”
Section: Immunotherapy Strategies For Ccamentioning
confidence: 99%
“…Some of the tumor-associated antigens (TAAs) that could be potential targets for peptide vaccines in CCA are MUC1 and Wilms’ tumor protein 1 (WT1). Finally, there are ongoing studies of Tumor lysate-based DC vaccines, which demonstrated an early invitro efficacy, while MUC1-loaded DC vaccine used as adjuvant treatment after the resection of biliary tract and pancreatic malignancies did not exert anti-MUC-1 antibody responses [ 159 , 160 ].…”
Section: Immunotherapy In Cholangiocarcinomamentioning
confidence: 99%